Characterization of (La,Sr)(Ti,Co)O3 Oxides for Symmetrical Solid Oxide Fuel Cell Electrodes - Napolitano, Federico Ricardo (2013)
In this work, a combined synchrotron X-ray diffraction (XPD), X-ray absorption near edge spectroscopy (XANES) and Extended X-ray Absorption Fine Structure (EXAFS) study of La0.4Sr0.6Ti1-yCoyO3±δ (0 ≤ y ≤ 0.5), intended as symmetric solid oxide fuel cells electrode, is presented. Charge compensation mechanisms were characterized by room temperature measurements; LSTC has a perovskite pseudocubic structure with an A-site vacancy concentration related with Co doping level. This result seems to be triggered by the fact that Ti remains in a higher formal valence (around 4+) independent of the Co concentrations. On the contrary, Co K-edge XANES spectra show a dependency with the doping level but this seems to be related to structural changes. In-situ measurements simulating a symmetric SOFC working environment show that LSTC undergoes a rhombohedral to cubic perovskite phase transition with critical temperature dependent of the structural distortion level.